1998
DOI: 10.1002/(sici)1098-2337(1998)24:6<421::aid-ab3>3.3.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Extremes of self‐esteem and narcissism and the experience and expression of anger and aggression

Abstract: This study examined the level of self-esteem and narcissism as personality variables involved in the disposition to experience and express anger. Three hundred thirty-eight subjects were sampled across two higher education centres and one student teaching programme in the United Kingdom. It was reasoned that individuals with both high self-esteem and narcissism would report especially high tendencies to experience and express anger and aggression and that those with high self-esteem and low narcissism would re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
53
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 24 publications
(34 reference statements)
7
53
0
2
Order By: Relevance
“…As a result, many interventions for antisocial and aggressive youth focus on enhancing the youth's self-image (e.g., Tebbutt et al, 1997). However, these interventions are potentially problematic in the light of other empirical studies which show that the tendency to act aggressively and to show disregard for the rights of others may be associated with inflated self-esteem or self-esteem blown to narcissistic proportions (Baumeister et al, 1996;Bushman & Baumeister, 1998;Papps & O'Carroll, 1998;Raskin et al, 1991).…”
supporting
confidence: 67%
“…As a result, many interventions for antisocial and aggressive youth focus on enhancing the youth's self-image (e.g., Tebbutt et al, 1997). However, these interventions are potentially problematic in the light of other empirical studies which show that the tendency to act aggressively and to show disregard for the rights of others may be associated with inflated self-esteem or self-esteem blown to narcissistic proportions (Baumeister et al, 1996;Bushman & Baumeister, 1998;Papps & O'Carroll, 1998;Raskin et al, 1991).…”
supporting
confidence: 67%
“…Research supporting this relationship indicates that self-esteem has a negative relationship with aggression (Murphy, Stosny, & Morrel, 2005) and the number of violent offense committed by violent criminals. In addition, researchers have revealed that the construct of narcissism moderates the relationship between self-esteem and violent criminality (Bushman & Anderson, 2002;Papps & O'Carroll, 1998;Sullivan & Geaslin, 2001). More specifically, narcissists tend to aggress against others when their self-esteem is threatened (Bushman & Anderson, 2002;Kirkpatrick, Waugh, Valencia, & Webster, 2002;Papps & O'Carroll, 1998).…”
mentioning
confidence: 99%
“…Although the link between narcissism and aggression has largely been investigated in adults (e.g., Bushman & Baumeister, 1998;Papps & O'Carroll, 1998), a preliminary study of narcissism in children indicated that self-reported narcissism was associated with conduct problems, especially for children who also reported low self-esteem . An additional study with early adolescents found that specific aspects of narcissism were associated with aggressive behavior and internalizing symptoms (Washburn et al, 2004).…”
mentioning
confidence: 99%